MEANING NEGOTIATION PRACTICE IN A READING CLASSSROOM: A CLASSROOM DISCOURSE ANALYSIS PERSPECTIVE - Santiara Afifatun Nisa (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2016)
Abstract: Classroom Discourse Analysis is very central study in main target of learning process. Its perspective can be focused on discussing negotiating meaning through spoken interaction in reading classroom between teachers and students as learning agents. Meaning negotiation is a form of give and take, whose purpose is to get a solution that have not already existed in participant’s opinion, but eventually it is acceptable for all. This thesis is descriptive qualitative analysis which primary sources of data are conducted through observation in trailblazer 6 class at Cirebon Local language school. Turn-taking presented in constructing knowledge in apperception structured by knowledge oriented exchange that got 78% and action oriented exchange got 22%. The process of exchange here indicates students’ need to recognize topic of their lesson; it means teacher should produce exchange in verbal type to construct students’’ knowledge. The dynamic moves that interpret in meaning making system in the data presentation from experiential meaning realize by material process of knowledge oriented exchange that got 82%. It means most of utterance realized by teacher is to describe content of their lesson to the students. Then, from interpersonal meaning most of their interactional process realized by 44% types of dynamic move rephrase that indicates asking of some information whether it came from the teacher or the students. The last action oriented exchange realized by 18%. It means most of utterances’ indicate subject as act of superstition experiences.  Keywords: Classroom Discourse, Reading cycles, Meaning negotiation, turn allocation, turn taking, dynamic moves.